2000
DOI: 10.1108/00035590010351503
|View full text |Cite
|
Sign up to set email alerts
|

A study of lead silicate glass degradation behaviour with reference to glass‐to‐metal seal applications

Abstract: Investigates the chemical resistance properties of lead silicate glasses suitable for compression‐type glass‐to‐metal (GM) seals, to aggressive solvents, containing different amounts of Na, K, and Ba as modifier ions, in acidic and alkaline media. In general attack rate was observed to be higher in alkaline medium, with maximum dissolution of 53.35 mg/cm2 compared to the maximum of 10.6mg/cm2 in acidic medium after 50 hour exposure. An increase in the concentration of BaO was found to decrease the degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This may be due to higher etching rate caused by favourable surface conditions such as an increase in etching, number of pits, etc. It may be noted that the dissolution rate in 5 per cent HCl at 90°C after 50 h was found to be much less compared to that observed in lead silicate glass (Kothiyal et al , 2000). It is believed that in acidic medium, the hydronium ions attack the modifier ions present at the interstitials of the glass network (Budd, 1961) as shown in equation (1).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This may be due to higher etching rate caused by favourable surface conditions such as an increase in etching, number of pits, etc. It may be noted that the dissolution rate in 5 per cent HCl at 90°C after 50 h was found to be much less compared to that observed in lead silicate glass (Kothiyal et al , 2000). It is believed that in acidic medium, the hydronium ions attack the modifier ions present at the interstitials of the glass network (Budd, 1961) as shown in equation (1).…”
Section: Discussionmentioning
confidence: 78%
“…Blagojevic and Grujic (1994) have reported that durability of lead borosilicate glasses is significantly improved by the substitution of part of SiO 2 by La 2 O 3 . In the study of degradation behaviour of lead silicate glass (Kothiyal et al , 2000); they have reported that an increase in BaO content led to the decrease in overall degradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…This increase of hydroxyl ions (pH > 7) is verified in the aqueous tests and in the liquid adsorbed to the glasses Pb15.50 and Pb15.60 after the high-humidity test. The increase of the pH accelerates the breaking of the SiO2 network through the reaction of dissolution (Reaction 4) 31,33,36,38,46 .…”
Section: Alteration Mechanismmentioning
confidence: 99%
“…Potassium ions in silicate glasses create non-bridging bonds [≡Si-O-K] that favor the ionexchange mechanism, leaving big channels of diffusion within the glass [31][32][33] . Also, the leached alkali favors the hygroscopicity of the glass surface 52 , accelerating the adsorption of environmental water to the glass surface, which increases the alteration rate.…”
Section: Influence Of the Compositionmentioning
confidence: 99%
See 1 more Smart Citation